EFEKTIVITAS SISTEM PENGENDALIAN INTERNAL PENJUALAN DI PT. ASTRA DAIHATSU CABANG DENPASAR SANUR - I Wayan Junaedi Setiawan; Ni Komang Sumadi; Cokorda Gde Bayu Putra (UNHI Press, 2021)
The study aims to fiind out how effectiveness is sales internal control sysstem at PT. Astra Daihatsu branch Denpasar Sanur. The method used to obtain data what is needed in preparing the report is the method interviews,documentation and literature studies while egineering data analysis used in this research in analysis qualitative. This analysis is done by collecting data regarding internal control, sales system and compare in with related theories. This research was conducted at PT. Astra Daihatsu branch Denpasar Sanur address at Jl. By Pass Ngurah Rai No.8 Pekandelan-Sanur Kaja south Denpasar Selatan district.The results of this study indicate that the implementation of the system internal sales control at PT. Astra Daihatsu branch Denpasar Sanur is already running pretty good where company has fifilled all five aspects based on system components internal control such as : 1). Control Environment 2). Risk Assessment, 3). Activity Controlling, 4). Information and Communication and 5). Monitoring.